2014
DOI: 10.5271/sjweh.3435
|View full text |Cite
|
Sign up to set email alerts
|

Job control and ambulatory blood pressure

Abstract: Objective: The effect of work on blood pressure (BP) in a general population with appropriate adjustment for confounders is not well defined. High job control has been found to be associated with lower BP and with nocturnal BP dipping. However, with older workers this may be compromised and has not been studied extensively. Methods: A cross-sectional study was carried out on a primary care-based sample (N=2047) aged 50–69 years. Data were collected on sociodemographic factors, medication, clinic, and ambulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…One earlier study has reported that low job control is related to higher asleep systolic BP and decreased nocturnal systolic BP dipping in younger hypertensive men (Fan et al 2013). In older workers, low control, measured by possibility for influence and development at work, has also been associated with higher asleep systolic BP, but not with systolic nocturnal BP dipping (Mc Carthy et al 2014). In our study, the differences in awake and asleep BP values and systolic nocturnal BP dipping between the low and high control groups remained small, even after performing a sensitivity analysis without participants on hypertensive medication.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…One earlier study has reported that low job control is related to higher asleep systolic BP and decreased nocturnal systolic BP dipping in younger hypertensive men (Fan et al 2013). In older workers, low control, measured by possibility for influence and development at work, has also been associated with higher asleep systolic BP, but not with systolic nocturnal BP dipping (Mc Carthy et al 2014). In our study, the differences in awake and asleep BP values and systolic nocturnal BP dipping between the low and high control groups remained small, even after performing a sensitivity analysis without participants on hypertensive medication.…”
Section: Discussionmentioning
confidence: 96%
“…However, it is unclear how job demands and job control separately associate with ambulatory BP and especially with nocturnal BP dipping in aging workers (Landsbergis et al 2013). Two previous studies have examined the relation of job strain and nocturnal BP dipping in middle-aged participants (Clays et al 2011;Fan et al 2013), and only one study (Mc Carthy et al 2014) with job control as the only exposure variable has focused on nocturnal BP dipping in the older workers (aged 50-69 years).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, over 100 years ago, Hayhurst (1915) explored the impact of occupational strain on outcomes like cardiac functioning. Today there are a wealth of studies analysing nervous system outcomes, particularly in relation to the physical drivers of wellbeing, such as the association between job control and blood pressure (McCarthy et al 2014), or between shift-work exposure (an aspect of workload and scheduling) and heart-rate variability (a biomarker of physical and mental health) (Bernardes Souza et al 2014).…”
Section: Nervous Systemmentioning
confidence: 99%
“…Blood pressure is a particularly significant parameter in this context. Positions involving a high level of personal responsibility have proven to contribute less to high blood pressure [ 6 ]. Incidence depends on age, sex, and BMI, with older employees in positions of high responsibility being more likely to develop cardiovascular diseases [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Positions involving a high level of personal responsibility have proven to contribute less to high blood pressure [ 6 ]. Incidence depends on age, sex, and BMI, with older employees in positions of high responsibility being more likely to develop cardiovascular diseases [ 6 ]. Physical fitness is an important parameter for coping with demands [ 7 ].…”
Section: Introductionmentioning
confidence: 99%